Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
To solve the given expression step-by-step, let's break it down and simplify it. The original expression is:
[tex]\[ 10x + 6 + 6 + 5 + 10 + 20 \times 30 \times 40 + 60 + 50 + 6 + 100x - 300 + 400 \times 500 + 60 \][/tex]
Let's start by simplifying the arithmetic operations.
1. Constants Multiplication:
- \( 20 \times 30 \times 40 \)
[tex]\[ 20 \times 30 = 600 \][/tex]
[tex]\[ 600 \times 40 = 24000 \][/tex]
- \( 400 \times 500 \)
[tex]\[ 400 \times 500 = 200000 \][/tex]
Now rewrite the expression replacing these products:
[tex]\[ 10x + 6 + 6 + 5 + 10 + 24000 + 60 + 50 + 6 + 100x - 300 + 200000 + 60 \][/tex]
2. Combine Like Terms:
Combine the terms involving \(x\):
[tex]\[ 10x + 100x = 110x \][/tex]
Now, combine the constants:
[tex]\[ 6 + 6 + 5 + 10 + 24000 + 60 + 50 + 6 - 300 + 200000 + 60 \][/tex]
Adding these step-by-step:
[tex]\[ 6 + 6 = 12 \][/tex]
[tex]\[ 12 + 5 = 17 \][/tex]
[tex]\[ 17 + 10 = 27 \][/tex]
[tex]\[ 27 + 24000 = 24027 \][/tex]
[tex]\[ 24027 + 60 = 24087 \][/tex]
[tex]\[ 24087 + 50 = 24137 \][/tex]
[tex]\[ 24137 + 6 = 24143 \][/tex]
[tex]\[ 24143 - 300 = 23843 \][/tex]
[tex]\[ 23843 + 200000 = 223843 \][/tex]
[tex]\[ 223843 + 60 = 223903 \][/tex]
So, the simplified expression is:
[tex]\[ 110x + 223903 \][/tex]
Thus, the final simplified form of the given expression is:
[tex]\[ 110x + 223903 \][/tex]
[tex]\[ 10x + 6 + 6 + 5 + 10 + 20 \times 30 \times 40 + 60 + 50 + 6 + 100x - 300 + 400 \times 500 + 60 \][/tex]
Let's start by simplifying the arithmetic operations.
1. Constants Multiplication:
- \( 20 \times 30 \times 40 \)
[tex]\[ 20 \times 30 = 600 \][/tex]
[tex]\[ 600 \times 40 = 24000 \][/tex]
- \( 400 \times 500 \)
[tex]\[ 400 \times 500 = 200000 \][/tex]
Now rewrite the expression replacing these products:
[tex]\[ 10x + 6 + 6 + 5 + 10 + 24000 + 60 + 50 + 6 + 100x - 300 + 200000 + 60 \][/tex]
2. Combine Like Terms:
Combine the terms involving \(x\):
[tex]\[ 10x + 100x = 110x \][/tex]
Now, combine the constants:
[tex]\[ 6 + 6 + 5 + 10 + 24000 + 60 + 50 + 6 - 300 + 200000 + 60 \][/tex]
Adding these step-by-step:
[tex]\[ 6 + 6 = 12 \][/tex]
[tex]\[ 12 + 5 = 17 \][/tex]
[tex]\[ 17 + 10 = 27 \][/tex]
[tex]\[ 27 + 24000 = 24027 \][/tex]
[tex]\[ 24027 + 60 = 24087 \][/tex]
[tex]\[ 24087 + 50 = 24137 \][/tex]
[tex]\[ 24137 + 6 = 24143 \][/tex]
[tex]\[ 24143 - 300 = 23843 \][/tex]
[tex]\[ 23843 + 200000 = 223843 \][/tex]
[tex]\[ 223843 + 60 = 223903 \][/tex]
So, the simplified expression is:
[tex]\[ 110x + 223903 \][/tex]
Thus, the final simplified form of the given expression is:
[tex]\[ 110x + 223903 \][/tex]
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.